ANALISIS PENGGUNAAN APLIKASI MOBILE BANKING PADA BANK BJB CABANG PALEMBANG MENGGUNAKAN METODE SWOT - Febi Dinata Yuda; Tri Oktarina (Abdi Jurnal Publikasi, 2025)
This service aims to support the use of the BJB DIGI mobile banking application in Palembang City through a digital education approach and feature innovation. Activities involve socialization to customers, identification of usage constraints, and training on application features. The results show that digital education improves customer understanding of the service, while strengthening technical infrastructure can minimize operational constraints. This strategy contributes to increasing customer loyalty and satisfaction.